2015
DOI: 10.1186/s13601-016-0097-8
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of the SQ-standardised grass sublingual immunotherapy tablet in patients treated with concomitant allergy immunotherapy: a non-interventional observational study

Abstract: Background The majority of allergic patients are poly-sensitized. For causal treatment by allergy immunotherapy (AIT) a single or few allergen products containing the clinically most relevant allergens are applied, but few data on tolerability of multiple application of AIT is available. The aim of our study was to investigate safety and tolerability in patients who started treatment by sublingual immunotherapy (SLIT) with the standardised SQ® grass SLIT-tablet and were treated with concomitant AIT products.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, these EVs may could subsequently be detected in a wide range of different organs, such as the heart, spleen, lungs, and brain ( 20 ). Hypothetically, breast milk miRNA could hence exert direct effects on immune regulation in the infant, for example by inhibiting the expression of key transcription factors in immune cell polarization ( 21 , 22 ) or epigenetic modifications in immune cell linages ( 23 , 24 ). Other regulatory ncRNA are also present in breast milk, such as long non-coding RNA (lncRNA), short interfering RNA (siRNA), piwi-interacting RNA (piRNA), circular RNA (circRNA) and fragmented tRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these EVs may could subsequently be detected in a wide range of different organs, such as the heart, spleen, lungs, and brain ( 20 ). Hypothetically, breast milk miRNA could hence exert direct effects on immune regulation in the infant, for example by inhibiting the expression of key transcription factors in immune cell polarization ( 21 , 22 ) or epigenetic modifications in immune cell linages ( 23 , 24 ). Other regulatory ncRNA are also present in breast milk, such as long non-coding RNA (lncRNA), short interfering RNA (siRNA), piwi-interacting RNA (piRNA), circular RNA (circRNA) and fragmented tRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…In a study with a similar design investigating the tolerability of the SQ ® grass SLIT-tablet applied with concomitant AIT, no change in the tolerability profile or increase in the frequency of adverse reactions compared with previous studies with the same product have been observed [ 5 ]. No concomitant AIT treatment has been recorded in 11.7% of patients treated with the primary SCIT.…”
Section: Discussionmentioning
confidence: 99%
“…The tolerability of treatment with the SQ ® grass SLIT-tablet when applied with concomitant AIT has been investigated in a separate study. No change in the tolerability profile and frequency of reactions with the SQ ® grass SLIT-tablet has been observed [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tolerability of treatment with the SQ Ò grass SLIT-tablet in adults and children [21,23], feasibility of an intra-seasonal start of treatment [22] and tolerability in patients treated with concomitant AIT [24] have been investigated in other studies in the real life setting. In our study, treatment satisfaction with the SQ Ò grass SLIT-tablet using the validated TSQM instrument was investigated in the real-life setting.…”
Section: Discussionmentioning
confidence: 99%
“…The SQ Ò -standardised grass sublingual immunotherapy (SLIT)-tablet contains a fast-dissolving extract of Phleum pratense (timothy grass; GRAZAX Ò ; ALK, Hørsholm, Denmark), which is indicated for the disease-modifying treatment of grass pollen-induced rhinitis and conjunctivitis in adults and children (5 years and older). The tolerability and efficacy of the tablet, including long-term efficacy and disease-modifying effect, has been demonstrated in several randomized controlled trials (RCTs) in Europe and USA [8][9][10][11][12][13][14][15][16][17][18][19][20], and tolerability in adults and children, health-related quality of life and feasibility of intra-seasonal start of treatment in real life have been documented in several non-interventional observational studies [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%